2003
DOI: 10.1038/sj.bjp.0705008
|View full text |Cite
|
Sign up to set email alerts
|

Unproductive cleavage and the inactivation of protease‐activated receptor‐1 by trypsin in vascular endothelial cells

Abstract: 1 Using fura-2¯uorometry of [Ca 2+ ] i in response to thrombin, trypsin and protease-activated receptor activating peptides (PAR-APs), we determined whether trypsin cleaves protease-activated receptor 1 (PAR1) and activates it in the endothelial cells of the porcine aortic valves and human umbilical vein. 2 Once stimulated with thrombin, the subsequent application of trypsin induced a [Ca 2+ ] i elevation similar to that obtained without the preceding stimulation with thrombin in the valvular endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…In contrast, when PAR 1 is fully glycosylated at Asn 75 , these cleavage sites are subsequently shielded by the attached oligosaccharide, and thus trypsin disarms WT hPAR 1 less efficiently. Interestingly, the previous study by Nakayama et al (9) reported that 100 nM trypsin cleaved PAR 1 but did not activate it in HUVEC cells, thus suggesting receptor disarming. We therefore assume that the glycosylation status of PAR 1 in HUVEC cells must be different from our PAR 1 -KNRK system.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, when PAR 1 is fully glycosylated at Asn 75 , these cleavage sites are subsequently shielded by the attached oligosaccharide, and thus trypsin disarms WT hPAR 1 less efficiently. Interestingly, the previous study by Nakayama et al (9) reported that 100 nM trypsin cleaved PAR 1 but did not activate it in HUVEC cells, thus suggesting receptor disarming. We therefore assume that the glycosylation status of PAR 1 in HUVEC cells must be different from our PAR 1 -KNRK system.…”
Section: Discussionmentioning
confidence: 90%
“…1). Furthermore, these residues are suggested to be cleaved by trypsin much faster than the residues Arg 41 -Ser 42 (9). Given that these two potential trypsin cleavage sites are located close to Asn 75 , it is not surprising that in the N62Q/N75Q and N75Q mutants, trypsin can gain easy access to these cleavage sites and therefore disarm these mutant receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of the tethered ligand region of PAR 1 by proteinases converts PAR 1 to the inactive conformation, thereby terminating the irreversibly persisted signals (Holinstat et al, 2009). Trypsin is one such proteinase and it removes the tethered ligand region of PAR 1 (Nakayama et al, 2004;Nakayama et al, 2003). The inhibition of the thrombin-induced sustained contraction by trypsin thus suggests the requirement of the active conformation of PAR 1 for the thrombin-induced sustained contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Trypsin can cleave fragments of PAR 1 at the thrombin cleavage site to activate this receptor (27), and high concentrations of bovine pancreatic trypsin can activate PAR 1 in cell lines (25,26). However, pancreatic trypsin also cleaves PAR 1 at sites distal to the tethered ligand, which would disable this receptor (27), and trypsin can inactivate PAR 1 in endothelial cells (54). Thus, trypsin IV may cleave PAR 1 at sites that would both activate and disable this receptor.…”
Section: Discussionmentioning
confidence: 99%